Behaviour of muslim consumer towards halal food products: a review and bibliometric analysis - Abdul Khader A.A Aneesh; Abbokar Siddiq (Journal of Halal Product and Research, 2024)
This study reviews factors affecting Muslim consumer behavior towards halal food products, using bibliometric analysis to identify key research trends and influential works in the field. A bibliometric analysis was conducted on 613 peer-reviewed articles from the Scopus database (2015-2024), using VOSviewer to visualize co-citation, keyword clusters, and research themes. The analysis reveals that religious beliefs, halal certification trust, and perceived product quality are key drivers of halal food purchasing behavior. Interest in halal products is growing globally, appealing to both Muslim and non-Muslim consumers due to perceived ethical and safety standards. The study identifies top contributors, influential journals, and leading countries in halal food research. Insights suggest further exploration into halal certification for alternative proteins, sustainability, and comparative studies across diverse regions. The findings are useful for researchers and businesses targeting the global halal market. This study provides a comprehensive bibliometric review of halal consumer behavior, highlighting trends and research gaps. It is essential for those seeking to understand the evolving dynamics of the halal food sector.